FSMP-06. IN VIVO MONITORING OF LDHA EXPRESSION IN GLIOBLASTOMA USING QUANTITATIVE EXCHANGED-LABEL TURNOVER 1H MRS TECHNIQUE. (25th March 2021) - Bagga, Puneet; Rich, Laurie; Haris, Mohammad; Wilson, Neil; Schnall, Mitch; Detre, John; Patay, Zoltan; Gajjar, Amar; Akers, Walter; Steinberg, Jeffrey; Krenciute, Giedre; Baker, Suzanne; et al.
Abstract: Most cancers, including glioblastomas (GBMs), rely extensively on glycolysis to support growth, proliferation, and survival. A hallmark of this elevated glycolysis is overexpression of Lactate dehydrogenase-A (LDHA) protein leading to increased uptake of glucose and overproduction of lactate. Various clinical trials using LDHA as a target for diagnosis and treatment have yielded encouraging results. However, in vivo monitoring of LDHA expression has been challenging due to either requirement of administration of radioactive substrates or specialized hardware. In this presentation, we will demonstrate a new method-quantitative exchanged-label turnover MRS (QELT, or simply qMRS)-that increases the sensitivity of magnetic resonance-based metabolic mapping without the requirement for specialized hardware. qMRS relies on the administration of deuterated ( 2 H-labeled) substrates to track the production of downstream metabolites. Since 2 H is invisible on 1 H MRS, replacement of 1 H with 2 H due to metabolic turnover leads to an overall reduction in 1 H MRS signal for the corresponding metabolites. We applied our qMRS technique to monitor the rate of lactate production in a preclinical GBM model. Infusion of [6, 6'- 2 H2 ]glucose led to downstream deuterium labeling of lactate, thereby resulting in a reduction in the 1.33 ppm lactate-CH3 peak on 1 H MRS over time. The subtraction of post-administration 1 H MR spectra from the pre-infusion spectra aided in the determination of the kinetics of the lactate turnover. We believe that the detection and quantification of lactate production kinetics may provide crucial information regarding tumor LDHA expression non-invasively in GBMs without requiring biopsies. Hence, qMRS is expected to open up new opportunities to probe LDHA expression differences in a variety of gliomas, including GBMs and astrocytomas. This method takes advantage of the universal availability and ease of implementation of 1 H MRS on all clinical and preclinical magnetic resonance scanners.